Symposium 9: Ethnomethodology as an Approach to Researching Networked Learning - Fox, Stephen (Proceedings of the International Conference on Networked Learning, 2008)
It is forty years since the publication of Studies in Ethnomethodology (Garfinkel, 1967), and recent years have seen something of a resurgence of interest in ethnomethodology from management and organization theorists, at least. Within the ‘practice turn’, there is a strong thread of ethnomethodologically informed ethnographic studies. In contrast to the ethnographic studies, marshalled in the formulation of situated learning theory (Lave and Wenger, 1991), these ethnomethodologically-informed ethnographic studies have not been aggregated to formulate an overarching theory of workplace practices, or learning. Rather, each produces a unique insight into the specifics of situated practices studied through this approach. In this paper I want to argue that ethnomethodology has a unique contribution to make to the study of networked learning practices amongst other kinds of learning, and will illustrate by discussing a case study of audio-visual learning resources provided for science educators via a national programme of teleconferences, examined in MacBeth (2000), which I would argue is a form of networked learning.